Museology as a pedagogy for heritage - Bruno, Maria Cristina Oliveira (2013)
This essay presents some parameters for the study of Museology and its respective contribution for the constitution of preservationist processes, biased towards heritage education. From the decoding of some parameters that delimit this applied discipline’s action and reflection field, the text presents some paradigms, which have stimulated its epistemological construction and have guided its social functions. These paradigms are considered responsible for a new methodological order within the scope of the museum and, further, for the new commitments that these institutions have taken up.